MESIN DISPENSER PAKAN OTOMATIS HEMAT ENERGI - fauzi, ahmad ilham; Hiron, Nurul; Busaeri, Nundang (Teknik Elektro Universitas Siliwangi, 2020)
Feeding is one of the important thing in the case of fish cultivation and harvesting the high population mobility in Indonesian still cannot be matched by the availability of production, nowadays, in general feeding is still depending on direct human help, so that people now just found a new technique to feed fish, runs and operates the tools automatically regarding to time and schedule that is provided or based on operation time of period they wanted and how much they want to feed. With the technology advancement, i would try to create innovating feeding machine with the mechanic system, make the feeding can be programmed and the duration of feeding can be controlled. By way of vertical valve modeling that works when getting an order from arduino UNO, so that once the valve opening with opening anggle 0o to 45o, 0o to 90o, 0o to 180o only requires a short duration making the required power more efficient.Keyword : Arduino Uno, Feeding, Mechanic, Valve